Market Women: Lessons Learned from Successful Black Women Entrepreneurs - Cheryl A. Smith (Adult Education Research Conference, 2002)
The purpose of this research was to explore the learning and business strategies of successful Black women entrepreneurs. The fundamental assumption of the study was that the life experiences of this underresearched group has value and worth and can provide useful lessons for adult learners, educators and entrepreneurs regardless of race, ethnicity or gender.